Assessment of water yam (Dioscorea alata L.) landrace varieties for resistance to anthracnose disease - Bakayoko, L.; Pokou, D.N.; Essis, B.S.; Kouakou, A.M.; Dibi, K.E.B.; Kouassi, A.B.; Nzue, B.; Koutouan, T.T.; Zohouri, P.G.; N'guetta, A.S.; Agre, A.P.; Mondo, J.; et al. (Academic Journals, 2022)
Yam anthracnose disease (YAD), caused by the fungus Colletotrichum gloeosporioides Penz, is the most damaging fungal disease of Dioscorea alata yam worldwide. Local yam varieties, which sustain Côte d'Ivoire’s farmers and other end-users livelihoods, are highly susceptible to this pathogen. Thus, there is a need for developing new yam cultivars to sustain yam production in Côte d'Ivoire. To achieve such objective, identifying and selecting sources of resistance within the existing germplasm is crucial prior to the establishment of a breeding program. This study, therefore, aimed at determining the field resistance to C. gloeosporioides of 115 D. alata landrace varieties. Field experiments were conducted at the Research Station for Food Crops (SRCV) of the CNRA, Bouaké City, in Central Côte d'Ivoire, for three growing seasons. Results showed that symptoms of the anthracnose disease were more noticeable four months after planting (P3): high disease severity and incidence scores. At this period, ‘Betebete’ group (DSS = 3.40 and DI = 99.81%) was the most sensitive to anthracnose disease across years. In contrast, ‘Brazo’ (DSS = 2.24 and DI = 94.81%) and ‘Florido’ (DSS = 2.59 and DI = 97.23%) groups were the least sensitive. This finding indicates that local yam accessions from Côte d’Ivoire have different sensitivity levels to anthracnose disease attacks. Therefore, the genetic diversity from this work should be further exploited by yam breeding and genetic improvement programs for developing cultivars, combining resistance to YAD, high yield potential, and superior tuber quality to meet producers and consumers’ needs.